Reef Fish in the Mudflats of Kaledupa Island in Wakatobi National Park, Indonesia - Ernik Yuliana; Adi Winata; Hasan Eldin Adimu; Yuni Tri Hewindati; Wibowo A. Djatmiko (HAYATI Journal of Biosciences, 2022)
Although frequently described as low-fertility or low-productivity habitat, coastal mudflats serve as important feeding grounds for fish. Many fish species from adjacent coral reefs, seagrass beds, or mangroves foraging periodically in mudflats. Because of this foraging behaviour, some local fishermen are known to utilize the mudflats to catch fish. However, the impact of this catching activities to the ecosystem has not been fully discovered. An examination of the fish community structure and levels of environmental stress had carried out in the mudflat ecosystem of the coast of Kaledupa Island in Wakatobi National Park (WNP), Indonesia. Two mudflat study sites were selected from the shore of Balasuna and Tampara villages located between mangroves and coral reefs. Data were sampled from the fish catch of local fishermen using fish fences (sero) installed in each mudflat area. Fish community structure was analyzed using diversity index and index of relative importance (IRI). ABC curves and species exploitation rate were used to assess the local environmental pressure. A total of 74 fish species were recorded from the mudflats of Kaledupa, which was found to be dominated by reef-associated fish species, comprising 63 species and accounting for 85% of the total catch. Additionally, although both sites had relatively high reef fish diversity, the obtained Clarke’s W-statistic values were approximately 0, indicating that the local fish communities presented moderate levels of disturbance. Three out of five fish species with the highest IRI values were found to be over-exploited, namely Siganus canaliculatus, Lethrinus ornatus, and Lethrinus variegatus.